Body injuries in male morphotypes of the Amazon River prawn (Macrobrachium amazonicum): Injuries in freshwater prawns. Issue 5 (17th November 2021) - Nogueira, Caio Santos; Carvalho-Batista, Abner; Teodoro, Sarah de Souza Alves; Costa, Rogerio Caetano; Alberto Farinelli Pantaleão, João
ABSTRACT: Fights between individuals in a population can be motivated by several factors, such as disputes over food, shelter and sexual partners. The present study aimed to evaluate the pattern of injury occurrence in the Amazon River prawn ( Macrobrachium amazonicum ). Prawns and environmental factors were sampled monthly, from February 2012 to September 2013, in the Tietê River, São Paulo, Brazil. Individuals were classified into eight different demographic classes and analyzed macroscopically for body injuries, which were separated into four categories (0–4). From the 2, 234 prawns collected, 124 presented one or more types of physical damages. The males of dominant castes presented the highest amount of injuries, suggesting that these groups get involved more frequently in disputes. Possibly, reproductive events are a strong stimulus for the occurrence of fights in freshwater prawns since the greatest amount of injuries was observed in the period of reproductive peaks.